The Impact of Child Custody Laws on Child Well-being: A Comparative Study - Anish Koirala; Ramesh Shrestha; Nisha Gautam (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study examines how child custody laws across different legal systems affect child well-being in post-divorce families. By comparing custody arrangements in multiple countries, the research investigates outcomes related to children's psychological health, academic performance, and social stability. Findings suggest that shared custody arrangements generally yield better outcomes for children, though the impact varies with cultural and legal factors.